PENGARUH WORKLOAD TERHADAP BURNOUT DENGAN WORK LIFE BALANCE SEBAGAI MEDIATOR PADA EMPLOYED HOMEMAKERS - Jessalyn Shannie; Jimmy Ellya Kurniawan (ITB AAS Indonesia Surakarta, 2026)
The high rate of burnout among female employees, particularly employed homemakers (working individuals with dual domestic and professional roles), is a critical issue in Indonesia. This study aims to examine the influence of workload on burnout with work-life balance as a mediator among employed homemakers. This quantitative study employed a cross-sectional design, involving 112 respondents selected through purposive sampling. Data were collected using structured online questionnaires and analyzed using path analysis with hierarchical regression (JASP). The results proved that work-life balance acts as a full mediator and indicates that workload exerts no significant direct effect on burnout. These findings confirm that the primary pathway from work pressure to burnout is the disruption of work-life balance. Consequently, developing organizational policies that actively support employed homemakers work-life balance is essential for preventing burnout in dual-role workers.